O uso da aprendizagem móvel e técnicas de gamificação como suporte ao ensino de matrizes - Cremontti Filho, Jorge Luiz (Universidade Federal de Roraima, 2022)
The improvement in the quality of mathematics teaching is the result of several factors such as the qualification of teachers, the search for new pedagogical models and the inclusion of technology to learning processes.There is a large gap between the technology and the classroom, especially when it comes in public education, and it is this problem that this work seeks to contribute to alternative solutions. Taking advantage of the huge demand of mobile phones and the strong influence that this device has on young people, we seek to support our application conducting research on the pedagogical aspects of mobile learning and, because of the fascination exerted by digital games, we studied the techniques of gamification. In this context, it was developed an application questions and answers (QUIZ), according to the precepts of mobile learning and using the motivational resources of gamification. As mathematical topic was used matrices and determinants due to this matter be current and its range of applications. For the purpose to validate the goals was carried out an experiment with high school students of the College Application of the Federal University of Roraima, where after using the application has distributed a questionnaire to students and teachers. And with the tabulation of results, there was a brief review of some aspects of this work.